Coagulation status of critically ill patients with and without liver disease assessed using a novel thrombin generation analyser - Morrow, GB; Beavis, J; Harper, S; Baker, P; Desbourough, MJR; Curry, N; Stanworth, SJ; Laffan, MA (Wiley, 2020)
The liver synthesises the majority of pro‐ and anti‐ coagulant and fibrinolytic proteins, and during liver dysfunction synthesis of these proteins is reduced. The end point of conventional haemostatic tests, such as the prothrombin time (PT), occurs when only 5% of thrombin generation (TG) has taken place and is not sensitive to the effects of natural anti‐coagulants. The aim of this study was to determine whether TG in the presence of thrombomodulin (TM) provides more useful information about coagulation potential, in comparison to the PT. Analysis was performed on ST Genesia, a novel TG analyser from Diagnostica Stago. TG was measured using STG‐Thromboscreen; a reagent containing an intermediate concentration of human tissue factor (TF) ± rabbit TM to account for anti‐coagulant protein C activity. Platelet‐poor plasma (PPP) samples from the Intensive Care Study of Coagulopathy‐2 (ISOC‐2), which recruited patients admitted to critical care with a prolonged PT (3 seconds above the reference range). Despite a prolonged PT, 48.0 and 60.7% of patients in the liver and non‐liver groups had TG parameters within the normal range. Addition of TM reduced TG by 34.5 % and 41.8 % in the liver and non‐liver groups, respectively. Interestingly, fresh frozen plasma (FFP) transfusion had no impact on TG. Measurement of TG with addition of TM provides a more informative assessment of coagulation capacity and indicates that haemostasis is balanced in patients with liver disease during critical illness, despite conventional tests suggesting that bleeding risk is increased. ESSENTIALS • The end point of conventional haemostatic tests occur when only 5 % of thrombin generation has taken place and are insensitive to natural anti‐coagulants. • Thrombin generation performed on a fully automated analyser in the presence of thrombomodulin may provide a more accurate interpretation of an individual’s coagulation potential. • Patients with liver disease have balanced haemostasis and are not significantly different from those without liver disease. • Fresh frozen plasma transfusion did not alter a patients thrombin generation and may not be necessary for minor procedures.